Diamond Fraud Analysis in Detecting Financial Statement Fraud in Manufacturing Companies - Anita Ade Rahma; Anatia Agusti; Devi Edriani; Wellia Novita; Winda Afriyenis (Universitas Pendidikan Ganesha, 2022)
Business people must provide accurate and relevant information and be free from fraud that will mislead other parties. To provide appropriate information for users of financial statements, the preparation of these financial statements must be prepared as well as possible according to accurate data based on applicable accounting rules. This study aims to analyze the effect of financial stability, external pressure, industry nature, rationalization, and capability on financial statement fraud. This study uses secondary data. The design used in this research is causal research. The research population was conducted on all manufacturing companies that went public and were active on the Indonesia Stock Exchange (IDX) during the 2015-2019 period. The sampling technique used the purposive sampling method. According to the sampling criteria, a total sample of 63 companies was obtained from the observations in this study. The results of this study prove that financial stability and rationalization affect financial statement fraud. Meanwhile, external pressure, the nature of the industry, and the capability do not affect fraudulent financial statements.